Which Groups of Children Are at More Risk of Fatality during COVID-19 Pandemic? A Case-Control Study in Yazd, Iran - Behnam Shafaei; Zahra Nafei; Mehran Karimi; Nasrin Behniafard; Farimah Shamsi; Masoud Faisal; Amir Pasha Amel Shahbaz; Elahe Akbarian (Canadian Journal of Infectious Diseases and Medical Microbiology)
Introduction. The study aims to investigate the characteristics, comorbidities, laboratory findings, and clinical manifestations of under 18-year-old patients who died with the diagnosis of COVID-19 and determination of the most prevalent risk factors. Method. This case-control study was performed at a referral hospital in Yazd from March 2020 to August 2021. All patients under 18 years who were diagnosed through real-time RT-PCR, chest computed tomography, and the World Health Organization definition were divided into deceased and survived groups. The characteristics (age and sex), disease severity, comorbidities, laboratory findings, and clinical manifestations of the two groups were compared and analyzed using SPSS, version 18 (SPSS Inc., Chicago, III., USA). Results. A total of 24 patients in the deceased group and 167 patients in the survived group were compared. The highest mortality rate was observed in the age group of 1 month to 5 years, although no statistically significant relationship was found between age groups and the risk of mortality. Disease severity, dyspnea, low oxygen saturation on admission, length of hospital stays, and hospitalization history before the last admission were significantly correlated with mortality (P < 0.05). Lymphopenia increased the probability of mortality by more than two times (OR: 2.568; 95% CI (0.962–6.852)), but this was not the case for D-dimer and C-reactive protein. Furthermore, 27.5% of survived patients had normal chest CT scans, which was a statistically significant difference compared to the deceased patients (P: 0.031). Conclusion. Based on the findings of this study, dyspnea, low oxygen saturation, and lymphopenia are critical indicators for identifying high-risk children with COVID-19 and triaging them for better care and treatment.